2013
DOI: 10.1017/s0954579413000539
|View full text |Cite
|
Sign up to set email alerts
|

Precursors of adolescent substance use from early childhood and early adolescence: Testing a developmental cascade model

Abstract: This study examined developmentally-salient risk and protective factors of adolescent substance use assessed during early childhood and early adolescence using a sample of 310 low-income boys. Child problem behavior and proximal family risk and protective factors (i.e., parenting, maternal depression) during early childhood, as well as child and family factors and peer deviant behavior during adolescence were explored as potential precursors to later substance use during adolescence using structural equation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 98 publications
(159 reference statements)
7
59
0
1
Order By: Relevance
“…Moreover, there is a lack of research that considers multiple domains of risk for HRSB from early childhood. Therefore, adopting a developmental cascade approach, which examines the longitudinal interplay between proximal and distal influences on individual development over time, 20 24 Given strong theoretical and empirical ties between child and family risk and deviant peer affiliation and parental monitoring, 25,26 as well as between peers and monitoring during adolescence and later deviant behavior, 27,28 it is possible that similar developmental pathways are relevant for adolescent HRSB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is a lack of research that considers multiple domains of risk for HRSB from early childhood. Therefore, adopting a developmental cascade approach, which examines the longitudinal interplay between proximal and distal influences on individual development over time, 20 24 Given strong theoretical and empirical ties between child and family risk and deviant peer affiliation and parental monitoring, 25,26 as well as between peers and monitoring during adolescence and later deviant behavior, 27,28 it is possible that similar developmental pathways are relevant for adolescent HRSB.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, participants' endorsements of "getting someone else pregnant" are limited to only the pregnancies that participants were aware of. A final limitation of this study is that our measures of deviant peer affiliation and parental monitoring were target-rather than peer-or parent-reported; however, other studies have suggested that perceptions of peers' antisocial activities 24 and parenting 31 are associated with multiple types of adolescent high-risk health behaviors. Furthermore, perceptions of peers' behaviors are more highly correlated with risk behavior than peers' self-report 30 and adolescent perceptions of parenting have been shown to more accurately represent parental monitoring, because parents often overestimate their actual knowledge of their adolescent' s activities.…”
Section: Figurementioning
confidence: 96%
“…There was good internal consistency among the alcohol use items (α = .873). Previous studies have successfully used the SRD to measure adolescent substance use (e.g., Sitnick et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…In this way, both depression (Forbes & Dahl, 2012) and substance use (Koob & Le Moal, 2001) could co-occur through their common association with disrupted reward function. Alternatively, psychosocial factors such as parental psychological dysfunction and child conduct problems have been found to predict both cannabis use (Sitnick et al, 2014) and depressive symptoms (Zoccolillo, 1992), potentially serving as a common vulnerability.…”
mentioning
confidence: 99%
“…According to the Brazilian National Survey of Student Health (Pesquisa Nacional de Saúde do Escolar -PeNSE), carried out in 2012, 26.1% and 5.1% of adolescents between the ages of 13 and 15 had consumed alcohol or tobacco, respectively, in the 30 days prior to the interview, whilst 7.3% had tried some type of illicit drug at least once in their lives 3 . Substance use in adolescence is associated with substance use in adulthood, and it is a predictor of the future burden of substancerelated diseases 1,4,5 . The consumption of alcohol, tobacco and illicit drugs has been associated with several short-and long-term health problems, such as injuries, unprotected sex, cognitive deficits, mental health problems and premature death, caused mainly by traffic accidents, homicides and suicides 5,6,7,8 .…”
Section: Introductionmentioning
confidence: 99%